PARTISIPASI PETANI DALAM PELATIHAN PEMBUATAN PUPUK ORGANIK BERBASIS KOTORAN SAPI DI DESA KALIBOTO - Rusdiyana, Eksa; Cahyadi, Muhammad; Pramono, Ahmad; Budiman, Anatta Wahyu (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2020)
The objective of this study was to evaluate participation rate of farmer in the production of cattle dung-based organic fertilizer program at Kaliboto village. This study was action research using participatory rural appraisal (PRA) approach through community partnership program conducted by Universitas Sebelas Maret (UNS) team. The subject of this study was farmers who are actively taking a part during a year and half of program. They were incorporated in “Suka Maju” farmer group. The data was collected using interview technique, focus group discussion (FGD), and also observation. The result of this study showed that participation of farmer was categorized as moderate participation due to the program was well planned by UNS team, although farmers were involved in program scheduling. The farmer participation was high during program implementation which is indicated by the high number of farmers joint in the training session covering production to marketing of organic fertilizer. In addition, the participation rate of farmer was categorized as moderate in evaluating of the program which is indicated by the small number of farmers giving advices and inputs for program sustainability.